Integrative analysis of SEPN1 in glioma: Prognostic roles, functional implications, and potential therapeutic interventions - Zisong Wang; Danwen Wang; Xuanyu Wang; Yihang Xu; Yunhe Yuan; Yuxin Chen; Zhiqiang Li; Xiaoping Liu (PLoS ONE, 2025)
Background SEPN1, a selenoprotein involved in redox regulation and endoplasmic reticulum stress response, has an unclear role in cancer. This study aims to investigate the expression, prognostic significance, and tumor microenvironment (TME) relevance of SEPN1 across pan-cancer, with a particular focus on glioma. Methods We analyzed SEPN1 expression and prognosis using the TCGA pan-cancer cohort. SEPN1 in glioma was further examined using data from TCGA, CGGA, GEO, and ZN-GC cohorts, along with survival analysis, single-cell RNA sequencing analysis, and enrichment analysis. We developed an SEPN1-related risk score (SRS) based on SEPN1-related long non-coding RNAs and validated its prognostic value. Drug sensitivity data and connectivity map analysis identified potential anti-glioma drugs based on the SRS. Results We found that SEPN1 was significantly upregulated in glioma, associated with poor prognosis, functioned as an independent risk factor, and predominantly expressed in malignant glioma cells. Enrichment analysis indicated the involvement of SEPN1 in immune-related processes and signaling pathways. Suppressing SEPN1 in glioblastoma cells inhibited proliferation and induced G2/M arrest and apoptosis. The SRS demonstrated strong prognostic value and correlated with enhanced immune infiltration in the glioma TME. Potential anti-glioma drugs were identified based on the SRS. Conclusions SEPN1 emerges as a novel biomarker and therapeutic target in glioma, providing a basis for future development of targeted therapies.